condiciones que presenta el distrito de Cascas para su desarrollo ecoturístico. - Ibañez Castro, Heidi Johana (2013)
This final report entitled Conditions the district ecotourism Cascas for development. Its field of study natural tourism resources Cascas District located in the province Gran Chimu, La Libertad._x000D_ This project arises from the interest of research natural areas with favorable characteristics for development of ecotourism in the District in order to provide novel alternatives for development and diversify tourism Cascas._x000D_ To carry out the research took into account three points, the variety of resources category natural sites, proximity to the tourist center of Trujillo and basic tourist facilities._x000D_ District was chosen because it has Cascas tourism resources managed in the best way tourist influx could generate national and international level, for the purpose mentioned above, it is necessary that the resources of the area are inventoried, this being the point of departure for the development of ecotourism in Cascas. It also explains the accessibility Trujillo resort to Cascas district in which describes the current state which is access roads, as well as explaining the status of each section._x000D_ Similarly to give the attitude of the visitors against the development of ecotourism in Cascas. On the other hand we talk about the basic tourist facilities and the condition in which they found, which discourages visitors know this district as shown on your potential claim ._x000D_ The last I conclude that the district has elements favorable for the development of ecotourism in natural tourism resources , the same to be utilized in a planned and organized and thus develop new tourism products such as eco-tourism circuit different conventional boosting tourism in the north of the country .